2019
DOI: 10.1007/s10453-018-09555-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sclerotinia sclerotiorum airborne inoculum, the widespread agent of white mould disease

Abstract: A means to rationalize the use of fungicides for crop protection and to make agriculture friendlier to environment and human health is to develop disease-risk forecasting systems based on the assessment of airborne inoculum abundance. Sclerotinia sclerotiorum, the pandemic agent of white mould disease, is disseminated via the atmosphere in the form of ascospores. These airborne spores are the primary source of inoculum initiating the majority of epidemics. However for witloof chicory (Cichorium intybus var. fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“… 1, Fall, Willbur, et al (2018); 2, Willbur, Fall, Bloomingdale, et al (2018); 3, Reich, unpublished; 4, Leyronas et al (2019); 5, Jones et al (2012); 6, Mila et al (2003); 7, Fall, Boyse, et al (2018); 8, Foster et al (2011); 9, Qandah and del Río Mendoza (2011); 10, Bourdôt et al (2001); 11, Mila et al (2004); 12, Workneh and Yang (2000); 13, Reich et al (2017); 14, Matheron and Porchas (2005); 15. Shah et al (2019); 16, Bom and Boland (2000); 17, Ferraz et al (1999); 18, Twengström, Sigvald, et al (1998); 19, Twengström, Köpmans, et al (1998); 20, Grau and Radke (1984); 21, Blad et al (1978); 22, Kader et al (2018); 23, Schwartz and Steadman (1978); 24, Ficke et al (2018).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“… 1, Fall, Willbur, et al (2018); 2, Willbur, Fall, Bloomingdale, et al (2018); 3, Reich, unpublished; 4, Leyronas et al (2019); 5, Jones et al (2012); 6, Mila et al (2003); 7, Fall, Boyse, et al (2018); 8, Foster et al (2011); 9, Qandah and del Río Mendoza (2011); 10, Bourdôt et al (2001); 11, Mila et al (2004); 12, Workneh and Yang (2000); 13, Reich et al (2017); 14, Matheron and Porchas (2005); 15. Shah et al (2019); 16, Bom and Boland (2000); 17, Ferraz et al (1999); 18, Twengström, Sigvald, et al (1998); 19, Twengström, Köpmans, et al (1998); 20, Grau and Radke (1984); 21, Blad et al (1978); 22, Kader et al (2018); 23, Schwartz and Steadman (1978); 24, Ficke et al (2018).…”
Section: Resultsmentioning
confidence: 98%
“…For ascospores, most studies report no association with 3‐day to 3‐week air temperature summaries (Fall, Willbur, et al, 2018; Foster et al, 2011; Qandah & del Río Mendoza, 2011) or with air temperatures from the same day to 3 days prior to ascospore counts (Bourdôt et al, 2001; Leyronas et al, 2019). However, some studies found significant correlations with air temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations